RANCANG BANGUN & ANALISIS SISTEM SISTEM INFORMASI PERPUSTAKAAN MENGGUNAKAN MODEL WATERFALL (STUDI KASUS: STMIK WICIDA SAMARINDA) - Kusnandar Kusnandar (STMIK Widya Cipta Dharma, 2016)
UPT. Library of College Management of Informatika Computer (STMIK) Wicida Samarinda East Kalimantan, representing peripatetic library in the field of loaning of books library of which can support student science. All activity at library still conducted manually, that is by noting every activity at one particular jotter. Information system is a structure system which consists of components which is interaction to support activities to present information at one particular organization. Applying of information system at library can assist to facilitate activity of library, especially activity related to presentation of information at library. Waterfall represent a model taking activity of elementary process like specification, development, validation, and evolution, and him as different process phases like specification of conditions, scheme of software, implementation, examination, and so on. Applying of model of waterfall at library information system expected can facilitate in activity of library especially in activity of loaning transaction and return of library book. Library book given by label of code (NIPUS) and membership card given by member number to facilitate process identify member and book at time of activity of loaning transaction and return. This research is expected can be made as media to water down activity at library, especially at UPT. Library of College Management of Informatika and Computer (STMIK) Wicida Samarinda East Kalimantan.